STUDI TENTANG FUNGSI WARUNG KOPI BAGI MASYARAKAT DI KOTA BAGANSIAPIAPI - Gelora Cita; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Bagansiapiapi had so many coffee shops scattered roads in every town of bagansiapiapi. Coffee shops scattered roads in every town and every day is filled with visitors references mainly male. Sat in the shops coffee is a become a habit for the local community. People who were in the coffee shop of the join of various elements among the public. Problems in the research is that citizens who become visitors coffee shop in the town of bagansiapiapi, whatever the motivation of the community sat in the shops coffee and what are the functions of the coffee shops for people in bagansiapiapi.The purpose of this research is to find out who the citizens become visitors coffee shop in bagansiapiapi, would like to know the motivation and learning what the community sit in the shops coffee in bagansiapiapi, and want to discover and learn what are the `functions of the coffee shops for people in bagansiapiapi. This research uses Functional theory by Robert K Merton, This research method is descriptive qualitative informant selection techniques used in this study was accidental sampling, sampling technique using purposive sampling. Who become informants in this study were people who visit and sit diwarung coffee.Based on the results of the research community who visit there in coffee maker in shops bagansiapiapi as influenced by friends and neighbors, on the other hand also the price is affordable. Visitors coffee shop that exists in bagansiapiapi is dominated by men who made their living as entrepreneur. Of the many visitors on average aged 24-45 years and above. The main purpose of the community visit in the shops coffee is as a source of actual information, coffee shops a place to socialize, as a source of income, and on the other hand coffee shops also serve as a meeting place for visitors and business lobby coffee shop especially for people in the town of bagansiapiapi.Key words: Functional, folkways, coffee shop